Screen media use by Portuguese children in 2009 and 2016: a repeated cross-sectional study. (2nd January 2021) - Rodrigues, Daniela; Gama, Augusta; Machado-Rodrigues, Aristides M.; Nogueira, Helena; Silva, Maria-Raquel G.; Rosado-Marques, Vítor; Stamatakis, Emmanuel; Jago, Russ; Padez, Cristina
Abstract: Background: Few studies have examined how access to mobile media is disrupting more traditional forms of media use. Aim: To examine screen-time in 2009/10 and 2016/17 among children aged 3–6 years and assess potential socio-economic determinants of adherence to screen-time recommendations. Subjects and methods: Two independent cross-sectional studies included 6874 Portuguese children. Screen-time (including television, computer, tablet, and smartphone) and proxy measures to calculate socioeconomic position (SEP) were parent-reported using a standardised questionnaire. Screen-time and adherence to screen-time recommendations were calculated for both periods. Determinants of excessive screen-time were identified using adjusted logistic regression models. Results: In 2009/10 screen-time averaged 107 min/day for pre-school children and 149 min/day for school-aged children. In 2016/17 values were 142 min/day and 173 min/day, respectively. Screen-time allocated to television was the highest, independently of children's age. In 2016/17, mobile media use was common among pre-school (37 min/day) and school-aged children (43 min/day). Exceeding the recommended screen-time was more prevalent in boys than girls (adjusted odds ratio (aOR) between 1.02 and 1.59) and in children whose parents had lower education levels or were unemployed (aOR between 1.00 and 2.23). Conclusion: Screen-time was high among pre-school children, emphasising the need for earlier interventions, particularly among those from lower-SEP who had higher risk of exceeding the screen-time recommendations.